The usefulness of a crime harm index: analyzing the Sacramento Hot Spot Experiment using the California Crime Harm Index (CA-CHI) - Mitchell, Renée J. (Journal of experimental criminology, 2019)
This study introduces the California Crime Harm Index (CA-CHI) and explores in what context a Crime Harm Index is a meaningful measure, comparing crime count outcomes to the CA-CHI. I decouple violent and property crime to determine when harm is a better indicator of reduction rather than counts.